2021
DOI: 10.1371/journal.pone.0260355
|View full text |Cite
|
Sign up to set email alerts
|

Measuring anxiety related to COVID-19: Factor analysis and psychometric properties of the Arabic Coronavirus Anxiety Scale

Abstract: Literature reports that fear and anxiety related to the coronavirus (COVID-19) pandemic may be a significant factor in promoting adherence to health-protective behaviours. This study aimed to validate an Arabic version of the Coronavirus Anxiety Scale (CAS). Participants aged 18 to 58 years of age were recruited from a university population (students and staff) as well as via social media from 22 June to 18 July 2020 when the United Arab Emirates was under a partial government-instituted lockdown. They complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
1
3
0
1
Order By: Relevance
“…The internal consistency of the CAS' total scores (Cronbach's alpha = 0.95, McDonald's omega = 0.95, Spearman-Brown coefficient = 0.94) showed satisfactory internal consistency, parallel to those reported in the prior psychometric studies (Lee, 2020;Lieven, 2021;Vally and Alowais, 2021). The convergent and concurrent validity were conducted in this study.…”
Section: Discussionsupporting
confidence: 74%
“…The internal consistency of the CAS' total scores (Cronbach's alpha = 0.95, McDonald's omega = 0.95, Spearman-Brown coefficient = 0.94) showed satisfactory internal consistency, parallel to those reported in the prior psychometric studies (Lee, 2020;Lieven, 2021;Vally and Alowais, 2021). The convergent and concurrent validity were conducted in this study.…”
Section: Discussionsupporting
confidence: 74%
“…It can be used to identify probable cases of dysfunctional anxiety associated with the coronavirus. Currently, the CAS is translated into Portuguese ( 78 ), Korean ( 79 ), Bangla ( 80 ), Arabic ( 81 ), Turkish ( 82 ), Japanese ( 83 ), Cuban ( 84 ), Polish ( 85 ), Spanish ( 86 ), Chinese ( 87 ), and Brazilian ( 88 ).…”
Section: Discussionmentioning
confidence: 99%
“…The scale has been found to be a highly valid and reliable [ 31 , 32 ]. The scale was previously translated to the Arabic language by Vally and Alowais [ 33 ]. In the present study, the translated scale also demonstrated high internal consistency, with a Cronbach’s alpha of 0.92.…”
Section: Methodsmentioning
confidence: 99%